ANALISIS KESESUAIAN KAWASAN WISATA ALAM HATUSUA BEACH DI KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Billy B. Seipala; Yulianus Dominggus Komul (Universitas Lambung Mangkurat, 2023)
The suitability of natural tourism areas is a concept used to evaluate and determine whether a natural area can be used as an attractive tourist destination. One form of utilization of natural resources in the coastal area of Kairatu District is the tourist or recreational area of Hatusua Beach. The natural tourist area of Hatusua Beach beach is located in Hatusua Village, Kairatu District, West Seram Regency which is a private area that is managed privately. The Hatusua Beach tourist attraction consists of coastal and mangrove forest vegetation, a Wildlife Conservation Area and an area of traditional and cultural objects from the people of Hatusua Village. Potential Attractions of Hatusua Beach's natural attractions are very attractive, white sand and natural panoramas in the morning and evening are highly favored by tourists who come to visit. The Hatusua Beach tourist area has a value that is included in the S1 criteria in the analysis of the suitability of beach tourism land for the recreation category. Visitors' perceptions of the Hatusua beach tourist area reach 80% with natural and handmade potential and visitors feel comfortable when visiting the Hatusua beach tourist area. Accessibility The Hatusua Beach tourist area is easy to reach by tourists, the facilities and infrastructure in the Hatusua beach tourist area are also sufficient so that visitors who come can enjoy the existing facilities in the tourist area so that based on the analysis that has been made it can be said that Hatusua Beach natural tourism can be said to be very suitable to be developed.